2021
DOI: 10.5267/j.ac.2021.4.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of intellectual capital as a mediation of relationship between audit committee and real earnings management

Abstract: This study aims to examine the role of human capital, which is part of intellectual capital, as a mediator in the relationship between audit committee expertise and the number of audit committee meetings with real earnings management. This research is a quantitative study. The data source used is data from manufacturing companies in Indonesia. The sample selection technique used purposive sampling. The analysis technique uses path analysis. The results showed that the expertise of the audit committee had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The results show that intellectual capital has the greatest positive effect on audit quality, followed by auditor specialization, auditor characteristics, and board independence. This suggests that companies should prioritize investing in intellectual capital to improve audit quality, and also ensure that they use auditors who have relevant knowledge and characteristics [14], [15], [29]- [31]. Additionally, companies should encourage board independence to ensure that auditors can perform their duties without unhealthy influences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that intellectual capital has the greatest positive effect on audit quality, followed by auditor specialization, auditor characteristics, and board independence. This suggests that companies should prioritize investing in intellectual capital to improve audit quality, and also ensure that they use auditors who have relevant knowledge and characteristics [14], [15], [29]- [31]. Additionally, companies should encourage board independence to ensure that auditors can perform their duties without unhealthy influences.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that independent boards of directors are better able to build and maintain relationships with key stakeholders, which can facilitate the flow of information needed for high-quality audits. Additionally, studies by [30], [31] found that intellectual capital, particularly structural capital, mediates the relationship between auditor characteristics and audit quality. These studies show that auditors with higher levels of structural capital, such as technology and information systems, are better able to leverage those resources to provide higher audit quality.…”
Section: Intellectual Capital and Audit Qualitymentioning
confidence: 99%
“…Several institutions have designed their reports and statements without accounting standards to evaluate intellectual capital numerically [16]. One study investigated the relationship between the intellectual capital disclosure level and the mandatory adoption of international financial reporting standards (IFRS) [19], [31], [36], [37]. However, the study found no evidence that IFRS adoption significantly impacts the level of disclosure of intellectual capital, intangible assets, and knowledge assets [17].…”
Section: Standardsmentioning
confidence: 99%
“…Many studies have argued that a substantial argument against intangibles capitalization is earnings management (Triki-Damak, Halioui, 2013;Garanina, Nikulin, Frangulantc, 2016). This is because accounting for intangible assets includes a lot of discretion for managers (Ji, 2020) and intangible assets do not get enough attention from auditors (Istanti, Chariri, Juliarto, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%